ETHNOMATEMATICS TRADITIONAL GAMES “ENGKLEK” IN LEARNING MATHEMATICS ELEMENTARY SCHOOL - Ervinia Risti Waning Hiyum; Arissona Dia Indah Sari (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Mathematics is a subject that must be taken by students. Mathematics has become a part of human culture inherent from the past to the present. Ethnomatematics is a term for mathematical values that exist in everyday life. Ethnomatematics is a learning mathematics related to certain cultures. In addition, ethnomatematics can be used to apply mathematics in the context of the current cultural system and the natural environment. Indonesia has a variety of cultural wealth, including in terms of traditional games. Although traditional games are very popular because they are in demand by all levels of society, as time goes by, slowly traditional games began to be forgotten because of the emergence of online games that are more easily accessible in various situations and conditions. Inspiring this, the writer feels interested in expressing mathematical values in the context of traditional games, especially the crank game. This research is a descriptive qualitative research with an ethnographic approach, considering this research is rooted in the phenomenon of Indonesian culture, namely traditional games. The purpose of this study is to identify hidden mathematical values in traditional games, with the hope of supporting the preservation of the traditional game. The results of this study include the description of the crank game which includes mathematical aspects such as geometry, comparison, and opportunities. In addition, research also shows that the game crank can be used as a container to teach multiplication material on integers.